N-of-1 Trials in Neurology: A Systematic Review. (11th January 2022) - Stunnenberg, Bas C.; Berends, Joost; Griggs, Robert C.; Statland, Jeffrey; Drost, Gea; Nikles, Jane; Groenewoud, Hans; van Engelen, Baziel G.M.; Jan van der Wilt, Gert; Raaphorst, Joost
Abstract : Background and Objectives: To perform a systematic review of published N-of-1 trials (e.g., single patient crossover trials) in neurologic disorders, including an assessment of methodologic quality and reporting. Methods: We searched PubMed, MEDLINE, and Embase from inception date to the December 1, 2019, for reports on N-of-1 trials in neurologic disorders. Basic trial information on design, disease, intervention, analysis, and treatment success was extracted. Strengths and weaknesses of the N-of-1 trials were assessed with the Consolidated Standards of Reporting Trials extension for N-of-1 trials (CENT) 2015 criteria checklist and the Jadad score as measures of quality and reporting. Results: We retrieved 40 reports of N-of-1 trials in neurologic disorders (19 individual N-of-1 trials, 21 series of N-of-1 trials). Most N-of-1 trials were performed in neuromuscular and neurodegenerative/movement disorders. Unlike the majority of trials that studied the main symptom(s) of a chronic stable condition, 9 N-of-1 trials studied a stable chronic symptom of a progressive or acute neurologic disorder. Besides pharmacologic interventions, electric stimulation protocols and nutritional products were studied. A mean total CENT score of 20.88 (SD 9.10, range 0–43) and mean total Jadad score of 2.90 (SD 2.15, range 0–5) were found as methodologic measures of quality and reporting across all N-of-1 trials. Discussion: N-of-1 trials have been reported in numerous neurologic disorders, not only in chronic stable disorders, but also in progressive or acute disorders with a stable symptom. This indicates the emerging therapeutic area of N-of-1 trials in neurology. Methodologic quality and reporting of N-of-1 trials were found to be suboptimal and can easily be improved in future trials by appropriately describing the methods of blinding and randomization and following CENT guidelines. Because most N-of-1 trials remain unreported in medical literature, this systematic review probably represents only the tip of the iceberg of conducted N-of-1 trials in neurologic disorders. In addition to conventional trial designs, N-of-1 trials can help to bridge the gap between research and clinical care by providing an alternative, personalized level 1 evidence base for suitable treatments.